Omni-relevant and contingent membership categories in research interview and focus group openings. (April 2018) - Whitehead, Kevin A; Baldry, Kim
Research based on interviews and focus groups has been characterized by a shift toward treating them as objects of inquiry in their own right, rather than simply as data collection instruments for the purposes of providing insights into other phenomena of interest. In this article, we contribute to research in this area by examining phenomena at the intersection of openings of interactions and membership categorization, specifically in the context of interviews and focus group interactions. We do so by examining a set of recorded interview and focus group interactions, considering how categories belonging to different types of membership categorization devices (omni-relevant, contingently omni-relevant, and contingent) are treated as relevant and procedurally consequential, observably shaping participants' conduct in the openings of the interactions. Our findings demonstrate some ways in which these different types of membership categories surface in the moment-by-moment unfolding of these parts of the interactions.